Age, growth and maturity of the pelagic thresher Alopias pelagicus and the scalloped hammerhead Sphyrna lewini. Issue 1 (January 2015) - Drew, M.; White, W. T.; Dharmadi; Harry, A. V.; Huveneers, C.
<x xml:space="preserve">Abstract</x> Indonesia has the greatest reported chondrichthyan catches worldwide, with c.110, 000 t caught annually. The pelagic thresher (Alopias pelagicus) and scalloped hammerhead (Sphryna lewini) together comprise about 25% of the total catches of sharks landed in Indonesia. Age and growth parameters were estimated for A. pelagicus and S. lewini from growth‐band counts of thin‐cut vertebral sections. Alopias pelagicus (n = 158) and S. lewini (n = 157) vertebrae were collected from three Indonesian fish markets over a 5 year period. A multi‐model analysis was used to estimate growth parameters for both species. The models of best fit for males and females for A. pelagicus was the three‐parameter logistic (L∞ = 3169 mm LT, k = 0·2) and the two‐parameter von Bertalanffy models (L∞ = 3281 mm LT, k = 0·12). Age at maturity was calculated to be 10·4 and 13·2 years for males and females, respectively, and these are the oldest estimated for this species. The samples of S. lewini were heavily biased towards females, and the model of best fit for males and females was the three‐parameter Gompertz (L∞ = 2598 mm LT, k = 0·15) and the two‐parameter Gompertz (L∞ = 2896 mm LT, k= 0·16). Age at maturity was calculated to be 8·9 and 13·2 years for males and females, respectively. Although numerous age and growth studies have previously been undertaken on S. lewini, few studies have been able to obtain adequate samples from all components of the population because adult females, adult males and juveniles often reside in different areas. For the first time, sex bias in this study was towards sexually mature females, which are commonly lacking in previous biological studies on S. lewini. Additionally, some of the oldest aged specimens and highest age at maturity for both species were observed in this study. Both species exhibit slow rates of growth and late age at maturity, highlighting the need for a re‐assessment of the relative resilience of these two globally threatened sharks at current high levels of fishing mortality throughout the eastern Indian Ocean.